Places of Authentication in the Medieval Kingdom of Hungary: Recent Approaches Concerning the Fields of Ecclesiastical Society and Countrywide Competence - Ribi, András (Historical Studies on Central Europe, 2025)
Places of authentication (loca credibilia) were legal institutions regarded as specifically Hungarian. Due to the substantial volume of related documents—approximately one-third of the surviving diplomatic sources from medieval Hungary were issued by these institutions—, they have long been at the forefront of historical research. However, thanks to recent technological developments, particularly the DL–DF database of the Hungarian National Archive, researchers now have incomparably improved the opportunity to address both longstanding and newly emerging questions. For this reason, a thorough understanding of these institutions is crucial for the study of medieval Hungarian history. The first part of this paper summarises essential background knowledge on loca credibilia through a historiographical overview. The following sections explore three widely recognised and relatively new directions in current research, along with recent findings: 1. The application of place-of-authentication charters in the reconstruction of the personnel of the church institutions involved (cathedral and collegiate chapters, as well as convents); 2. The countrywide competence of some centrally located loca credibilia; these have been known for centuries, but have only recently become a subject of scholarly analysis due to previous difficulties in accessing the charters, and 3. An overview of the activities of the places of authentication at the beginning of the Early Modern era, a particularly turbulent period in Hungarian history marked by the double election of kings.